Pengaruh Laju Pertumbuhan Produk Domestik Bruto (PDB) dan Tingkat Upah terhadap Tingkat Pengangguran Terbuka di Indonesia: Studi Empiris Tahun 2015-2025 - Fiby Julianti Zarotun Ikhsan; Ecca Ratu Nurdiana; Widia Amanda Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study was conducted to identify and analyze the relationship between annual wages and gross domestic product on the open unemployment rate. This study employs a quantitative approach using multiple linear regression analysis. The data used in this study consists of secondary time-series data obtained from official publications of relevant agencies. Before the regression analysis was performed, the data was first tested using classical assumption tests, which included tests for normality, multicollinearity, autocorrelation, and heteroscedasticity. The results of the study indicate that the annual wage variable has a significant effect on the open unemployment rate, with a negative relationship. This suggests that an increase in annual wages tends to be accompanied by a decrease in the open unemployment rate. On the other hand, the gross domestic product variable does not show a significant effect on the open unemployment rate. Taken together, the annual wage and gross domestic product variables have not shown a significant effect on the open unemployment rate. The research results indicate that labor market factors, particularly labor income levels, play a greater role in influencing the unemployment rate than the economic growth rate. Therefore, government policies are expected to focus not only on increasing the economic growth rate but also on job creation and improving workers’ welfare to reduce the open unemployment rate.